Analisis Pengaruh Budaya Organisasi Terhadap Strategi Peningkatan Kualitas Sumber Daya Manusia Pada Persebaya Amatir - Elly Kharisma; Supriyono Supriyono (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract Organizational culture is a set of established norms that constitute the values or characteristics of a company. Organizational culture can shape, influence, and even reflect the quality of human resources. Employee orientation can create effective strategies to enhance development within it. This journal discusses the analysis of the influence of organizational culture on the improvement of Human Resources Quality, also known as resources, in Persebaya Amateur. The quality of human resources can experience improvement due to the influence of the organizational culture created within it. This research uses a direct survey method involving interviews with relevant parties. Data are analyzed using organizational culture as a crucial factor influencing the improvement of human resource quality in the company. The creation of quality human resources is a significant impact of a positive organizational culture. In general, this research aims to analyze the influence of organizational culture on the strategies used to improve human resource quality. This is also to measure the strategies and roles in regression techniques to assess the extent to which organizational culture influences the internal club development strategy. The research results indicate that a positive and strong contribution of organizational culture can enhance effectiveness in strategies and roles in improving human resource quality, which can be utilized for the internal development of the Persebaya Amateur Club. The implications of these findings create a foundation for amateur football clubs to enhance performance and its positive impact on overall club development. This study can provide guidance for other amateur football clubs that seek to strengthen key aspects within their organizations.